Stability of Anthocyanins, Phenolics and Color of Tart Cherry Jams - Josipa Vukoja; Anita Pichler; Mirela Kopjar (Foods, 2019)
The aim of this work was to assess the effect of a set storage period on the phenolics, anthocyanins, antioxidant activity, color, and texture of three types of jams made from tart cherry. The prepared samples of tart cherry jams were: (1) regular jam; (2) extra jam; and (3) light jam. The samples were stored at room temperature for eight months. Results of the investigated parameters after storage were compared with the results after sample preparations, and between the different jam samples. The light jam had the highest phenolic content and anthocyanin content (3.34 g/kg and 985.52 mg/kg). Consequently, the light jam had the highest antioxidant activity determined by ABTS (2,2’-azinobis(3-ethylbenzothiazoline sulfonic acid)) and DPPH (2,2-diphenyl-1-picrylhydrazil) method. After storage, the highest retention of the phenolics had regular jam and extra jam (85%), while the lowest retention (74%) were found in the light jam. Anthocyanin stability was the highest in the regular jam, then the extra jam (15%), and then the light jam, with retention of 22%, 15%, and 12%, respectively. Color parameters and textural parameters also depended on jam type, as well as on storage conditions. Since the investigated types of jams differed in content of fruit and water, these are the most important factors that cause the change in the retention of phenolics and anthocyanins, as well as a change in color and textural parameters.